Recognizing Human Activities Based on Wearable Inertial Measurements - Methods and Applications - Pekka Siirtola (International Journal of Interactive Multimedia and Artificial Intelligence, 2015)
On April 10 of 2015 Pekka Siirtola defended his PhD thesis, called “Recognizing Human Activities Based on Wearable Inertial Measurements - Methods and Applications” [1]. The thesis was supervised by Professor Juha Röning and pre-eximined by Associate Professors Ulf Johansson from University of Borås, Sweden, and Daniel Roggen from University of Sussex, United Kingdom. Pekka Siirtola successfully defended his thesis against his opponent Professor Barbara Hammer from University of Bielefeld, Germany. This publicly open defence was held in Auditorium TS101 at University of Oulu, Finland.